2019
DOI: 10.17116/stomat20199805111
|View full text |Cite
|
Sign up to set email alerts
|

Histological evaluation of inflammatory response to zinc-oxide-eugenol filling materials in a soft and bone tissues

Abstract: Цель исследования-оценка и сравнение интенсивности воспалительной реакции при введении материала на основе цинкоксид-эвгенольного цемента в костную и мягкие ткани челюсти. Материал и методы. Эксперимент был проведен на 20 кроликах. Пломбировочный материал на основе цинк-оксидэвгенольного цемента вводили в искусственно созданные дефекты в костной и мягких тканях челюсти кролика. На 14-е и 30-е сутки животных выводили из эксперимента. Изготавливали из фрагментов слизистой оболочки и челюсти гистологические препа… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Histological analysis reveals that zinc-oxide-eugenol-based filling material supports inflammatory reaction in the tissue, but bone tissue shows statistically lower inflammatory response in comparison to soft tissue (11).…”
Section: Discussionmentioning
confidence: 95%
“…Histological analysis reveals that zinc-oxide-eugenol-based filling material supports inflammatory reaction in the tissue, but bone tissue shows statistically lower inflammatory response in comparison to soft tissue (11).…”
Section: Discussionmentioning
confidence: 95%
“…Seo et al's research demonstrated that zinc treatment of osteoblastic MC3T3-E1 cells affected their proliferation, collagen synthesis, and the activity of the bone marker protein alkaline phosphatase (ALP) [25]. Furthermore, human studies indicate that oral administration of zinc at a dose of 3060 µmol/kg can increase alkaline phosphatase (ALP) activity and the DNA content of bone tissue [26,27].…”
Section: Introductionmentioning
confidence: 99%